2005
DOI: 10.1126/science.1120479
|View full text |Cite
|
Sign up to set email alerts
|

Torus-Margo Pits Help Conifers Compete with Angiosperms

Abstract: The unicellular conifer tracheid should have greater flow resistance per length (resistivity) than the multicellular angiosperm vessel, because its high-resistance end-walls are closer together. However, tracheids and vessels had comparable resistivities for the same diameter, despite tracheids being over 10 times shorter. End-wall pits of tracheids averaged 59 times lower flow resistance on an area basis than vessel pits, owing to the unique torus-margo structure of the conifer pit membrane. The evolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
186
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(196 citation statements)
references
References 2 publications
(1 reference statement)
4
186
0
2
Order By: Relevance
“…Because they allow comparable rates of water transport with fewer pits, torusand-margo tracheids are mechanically stronger than those of pycnoxylic Paleozoic woods. The torus-margo structure also allows for a tighter seal against embolism, if such events are rare; when subject to repeated embolism events, the torus may become stuck against the aperture, permanently sealing the tracheid against fluid flow (Hacke et al 2001b, Pittermann et al 2005, Pittermann et al 2006a, Pittermann et al 2006b, Sperry et al 1994, Sperry and Tyree 1990, Zimmermann 1983. Perhaps the tracheids observed today in conifers and Ginkgo present the optimum balance among mechanical support, cavitation avoidance, and water conductivity in plants developmentally committed to pycnoxylic wood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because they allow comparable rates of water transport with fewer pits, torusand-margo tracheids are mechanically stronger than those of pycnoxylic Paleozoic woods. The torus-margo structure also allows for a tighter seal against embolism, if such events are rare; when subject to repeated embolism events, the torus may become stuck against the aperture, permanently sealing the tracheid against fluid flow (Hacke et al 2001b, Pittermann et al 2005, Pittermann et al 2006a, Pittermann et al 2006b, Sperry et al 1994, Sperry and Tyree 1990, Zimmermann 1983. Perhaps the tracheids observed today in conifers and Ginkgo present the optimum balance among mechanical support, cavitation avoidance, and water conductivity in plants developmentally committed to pycnoxylic wood.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that there are significant differences between these two pit types when pit resistance is normalized to area; because of the large pores in the margo, conifers have pit area resistances up to two orders of magnitude lower than those of angiosperms (Pittermann et al 2005, Pittermann et al 2006a, Pittermann et al 2006b). Consequently, there are significant effects of pit membrane pore size on values of r p .…”
Section: Model Descriptionmentioning
confidence: 99%
“…Second, torus-margo pits of conifers with their valve-like closing mechanism (Hacke et al, 2004;Pittermann et al, 2005; Fig. 3), are likely responsible for separating air and water phases within the xylem, and thus for the required isolation of embolized conduits during the refilling process.…”
Section: Discussionmentioning
confidence: 99%
“…Just the isolation of embolized from functional conduits, which is another prerequisite for refilling (see above), probably does not require metabolic activity. Conifer pits act like valves, which are passively closed by aspiration of the torus to the porus of the pit chamber (Pittermann et al, 2005;Hacke and Jansen, 2009;Plavcová et al, 2014). This mechanism might be especially advantageous to ensure isolation during refilling.…”
mentioning
confidence: 99%
“…S1]. Because all of the water that ascends within conifer xylem must pass through the bordered pits of overlapping tracheids, pit characteristics are a major determinant of tracheid and whole xylem hydraulic conductance (11)(12)(13) and account for Ͼ50% of total xylem hydraulic resistance across a broad range of tracheid-and vessel-bearing species (14). The pit membrane of Douglas-fir and most other conifers is chemically and structurally unlike membranes in living cells: It contains the torus (a central impermeable thickening) surrounded by a thinner and porous margo that is mostly composed of encrusted cellulosic strands ( Fig.…”
mentioning
confidence: 99%